2014
DOI: 10.1002/adma.201306095
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Large‐Area 2D MoS2(1‐x)Se2x Semiconductor Alloys

Abstract: Semiconducting MoS₂(₁-x) Se₂x mono-layers where x = 0-0.40 are successfully grown over large areas. A random arrangement of the S and Se atoms and a tunable bandgap photoluminescence are observed. Atomically thin, 2D semiconductor alloys with tunable bandgaps have potential applications in nano- and opto-electronics. Field-effect transistors fabricated with the monolayers exhibit high on/off ratios of >10(5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
325
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(357 citation statements)
references
References 38 publications
(40 reference statements)
17
325
1
1
Order By: Relevance
“…CVD‐grown graphene has made great breakthrough in the growth of large‐area graphene 17, 155, 156, 157, 158, 159, 160. Recently, the synthesis of 2DLMs via CVD methods has been illustrated in many reports especially for MoS 2 ,30, 31, 161, 162, 163, 164, 165, 166, 167, 168, 169, 170, 171, 172, 173, 174, 175, 176, 177, 178, 179, 180, 181, 182, 183, 184, 185 which also shows promising applications in electronics and optoelectronics. Up to now, there are several reports on synthesizing 2D GIVMCs nanoflakes via CVD method, which is still at the initial stage.…”
Section: Preparation Methods and Characterizationsmentioning
confidence: 99%
“…CVD‐grown graphene has made great breakthrough in the growth of large‐area graphene 17, 155, 156, 157, 158, 159, 160. Recently, the synthesis of 2DLMs via CVD methods has been illustrated in many reports especially for MoS 2 ,30, 31, 161, 162, 163, 164, 165, 166, 167, 168, 169, 170, 171, 172, 173, 174, 175, 176, 177, 178, 179, 180, 181, 182, 183, 184, 185 which also shows promising applications in electronics and optoelectronics. Up to now, there are several reports on synthesizing 2D GIVMCs nanoflakes via CVD method, which is still at the initial stage.…”
Section: Preparation Methods and Characterizationsmentioning
confidence: 99%
“…The substrates were placed in a cold zone at 650 • C [46]. Feng et al [52] have also reported the synthesis of uniformly distributed monolayer MoS 2(1−x) Se 2x alloys on SiO 2 /Si substrates through the direct evaporation of MoSe 2 [44], (d,e) adapted with permission from Li et al [45], (f ,g) adapted with permission from Wu et al [46] and (h) adapted with permission from Liu et al [47].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…[1][2][3][4][5] Owing to their high anisotropy and unique crystal structures, MX 2 can be utilized in a variety of energy conversion and storage applications, including water splitting cells, rechargeable batteries, supercapacitors, fuel cells, as well as various electronic and optoelectronic devices, etc. [6][7][8][9][10][11] Nanoengineering (morphology, size, number of layers, edges, defects), [12][13][14][15][16][17] phase conversion, [18][19][20][21][22][23] and composition tuning (alloying, doping with foreign transition metal), [24][25][26][27][28][29][30][31] represent the hot research areas in the recent past, aiming at modulation of the material properties and improvement of the device performances. Such impressive progress benefits from the success in synthesizing nanostructured MX 2 with precisely controlled parameters including edge density and crystalline phase.…”
Section: Introductionmentioning
confidence: 99%